2018
DOI: 10.1186/s12887-018-1083-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of probable Attention-Deficit/Hyperactivity Disorder symptoms: result from a Spanish sample of children

Abstract: BackgroundThe aims of our study were to: (i) determine the prevalence of children aged 4 to 6 years with probable Attention-Deficit/Hyperactivity Disorder (ADHD) symptoms in the Spanish population; and (ii) analyse the association of probable ADHD symptoms with sex, age, type of school, origin (native or foreign) and socio-economic status in these children.MethodsThis cross-sectional study included 1189 children (4 to 6 years-old) from 21 primary schools in 19 towns from the Ciudad Real and Cuenca provinces, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 40 publications
1
7
1
3
Order By: Relevance
“…This could be due to the fact that Conners ECGI includes not only items about restlessness-impulsivity but also emotional lability, which may be more observable or higher in girls. There was a notably high rate of symptoms in the clinical range (Conners T ≥ 70) reported by parents in both pre-school (26.2%) and school-age children (34%, reaching a value of 42% in boys), which is clearly higher than the rates reported by other authors (Aboul-ata & Amin, 2018; Canals et al, 2018; Cao et al, 2018; Cerrillo-Urbina et al, 2018; Joshi & Angolkar, 2018; Yadegari et al, 2018). Although the high rate of symptoms detected in boys will be related to the high prevalence of ADHD in males (4% in pre-schoolers and 11.9% in school-age children), it could also be due to the characteristics of the screening test used to assess the risk symptoms (Conners ECGI and Conners 3 ADHD Index).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…This could be due to the fact that Conners ECGI includes not only items about restlessness-impulsivity but also emotional lability, which may be more observable or higher in girls. There was a notably high rate of symptoms in the clinical range (Conners T ≥ 70) reported by parents in both pre-school (26.2%) and school-age children (34%, reaching a value of 42% in boys), which is clearly higher than the rates reported by other authors (Aboul-ata & Amin, 2018; Canals et al, 2018; Cao et al, 2018; Cerrillo-Urbina et al, 2018; Joshi & Angolkar, 2018; Yadegari et al, 2018). Although the high rate of symptoms detected in boys will be related to the high prevalence of ADHD in males (4% in pre-schoolers and 11.9% in school-age children), it could also be due to the characteristics of the screening test used to assess the risk symptoms (Conners ECGI and Conners 3 ADHD Index).…”
Section: Discussioncontrasting
confidence: 56%
“…For 2017, they estimated a prevalence of 4.06% (5.81% for boys and 2.20% for girls). However, at the general population level, epidemiological studies carried out to date have mostly provided prevalence estimates at the level of ADHD risk symptoms on the basis of parent and teacher reports or DSM-III-R/DSM-IV data (Canals et al, 2018; Catalá-López et al, 2012; Cerrillo-Urbina et al, 2018; Jiménez et al, 2015; Marín-Méndez et al, 2018). The meta-analysis by Catalá-López et al (2012) estimated an overall pooled prevalence of ADHD of 6.8% in school-age children.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to our finding, Cerrillo-urbina et al, 2018 found that the inattentive type is the most frequently seen subtype. This may be due to different methods and sampling in this study [26].…”
Section: Discussionmentioning
confidence: 90%
“…Estos patrones están presentes en al menos dos contextos del niño o adolescente (familiar, social y académico) y a menudo condu-cen a un trastorno en el desarrollo de la coordinación (de Gregorio, Pérez y Moro, 2019) y/o un bajo rendimiento académico y dificultades en las habilidades sociales (DSM-V, 2014; Mezcua-Hidalgo, Ruiz-Ariza, de Loureiro, y Martínez-López, 2020; Pulido y Ramírez Ortega, 2020). El TDAH es diagnosticado aproximadamente en el 2 -7% de la población escolar, debiéndose esta variación al empleo de diferentes métodos de diagnóstico (Sayal, Prasad, Daley, Ford y Coghill, 2018), en España alcanza aproximadamente el 5,4%, (Canals et al, 2018;Cerrillo-Urbina et al, 2018), coincidiendo con la prevalencia mundial.…”
Section: Introductionunclassified